Optimalisasi Kepuasan Kerja Guru - Hardianto, Hardianto (Universitas Kristen Satya Wacana, 2018)
ACDP (Analytical and Capacity Development Partnership) data suggests that 10% of teachers did not attend school and 14% of those attending did not attend the class. This number indicates the teacher is not satisfied with their work. Teacher job satisfaction needs to be improved so that education can run better. Teachers who are satisfied at work will feel happy with their work, happy with the work environment and so on. Unsatisfied teachers can cause low performance and even increase the desire to move or stop working. Therefore, efforts need to be made to optimize teacher work satisfaction. Two ways that can be done to improve teacher job satisfaction are by giving appropriate rewards and increasing motivation.